Morbidity and Mortality Among Adults Experiencing Homelessness Hospitalized With COVID-19. (16th May 2021) - Cha, Susan; Henry, Ankita; Montgomery, Martha P; Laws, Rebecca L; Pham, Huong; Wortham, Jonathan; Garg, Shikha; Kim, Lindsay; Mosites, Emily; ,
Abstract: People experiencing homelessness (PEH) are at higher risk for chronic health conditions, but clinical characteristics and outcomes for PEH hospitalized with coronavirus disease 2019 (COVID-19) are not known. We analyzed population-based surveillance data of COVID-19–associated hospitalizations during 1 March to 31 May 2020. Two percent of the people hospitalized with COVID-19 for whom a housing status was recorded were homeless. Of 199 cases in the analytic sample, most were of racial/ethnic minority groups and had underlying health conditions. Clinical outcomes such as ICU admission, respiratory support including mechanical ventilation, and deaths were documented. Hispanic and non-Hispanic black persons accounted for most mechanical ventilation and deaths. Severe illness was common among persons experiencing homelessness who were hospitalized with COVID-19.